How Effective is Macroprudential Policy? : Evidence from Lending Restriction Measures in EU Countries - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2019)
This paper assesses the effectiveness of lending restriction measures, such as loan-to-value and debt-service-to-income ratios, in affecting developments in house prices and credit. We use data on 99 lending standard restrictions implemented in 28 EU countries over 1990-2018. The results suggest that lending restriction measures are generally effective in curbing house prices and credit. However, the impact is delayed and reaches its peak only after three years. In addition, the impact is asymmetric, with tightening measures having weaker association with target variables compared to loosening measures. The association is stronger in countries outside of euro area and for legally-binding measures and measures involving sanctions. The results have practical implications for macroprudential authorities.